Pengaruh Pendidikan Kesehatan Tentang Nutrisi Gizi Seimbang Dengan Perilaku Pencegahan Anemia Pada Remaja - Fitriani Fitriani; Ridni Husnah (Jurnal Ners, 2023)
Anemia is an indicator of poor nutrition and health. Anemia does not only have an impact on individual health status but will also have an impact on other global nutritional problems such as stunting, wasting, underweight and low birth weight. Malnutrition caused by anemia can affect school performance in children and reduced work productivity in adults. The consequences of anemia can have further social and economic impacts on individuals and families. This research is a quasy experimental pre-post test with control group design with a total sample of 35 adolescents aged 15-28 years. The research was conducted on Panjang Island in July 2023. Attitudes of young women on Panjang Island in preventing anemia before being given health education, most were in the bad category as many as 19 respondents (54%). After adolescents were given health education, the most good category was 19 respondents (54%). The statistical test results obtained P-value = 0.003 that it was concluded that there was an influence of health education on balanced nutrition with anemia prevention behavior in adolescents on Panjang Island in 2023.